Biochemical study of idebenone effect on mitochondrial metabolism of yeast - Chapela, Sebastián Pablo (2008)
The aim of this work was to study the effect of the drug idebenone on the growth of a strain of Saccharomyces cerevisiae yeast and its respiratory-deficient mutant (rho0). We took this yeast as a model system of the interaction of the drug with mammalian cells. The effect of idebenone was evaluated in rich and minimal media. In the S288c strain, idebenone exerted a growth inhibitory effect in concentrations higher than 50 μM in media containing a carbon source consumed at mitochondrial level. In conditions of low oxygen supply, idebenone allows yeast to keep a cellular yielding comparable with conditions of normal oxygen supply. Also, the presence of idebenone in the growth media increased by 50% the fluorescence signal of rhodamine 123, indicating a higher mitochondrial membrane potential. The results could explain the effect of idebenone in the treatment of diseases in which oxygen deficiency alters the energetic metabolism of the cell.